Zinc oxide varistor ceramic and preparation method and application thereof
By optimizing the formulation and preparation process of zinc oxide varistors, their density, grain uniformity, and macroscopic electrical properties are improved, solving the application problems of zinc oxide varistors in medium and high voltage power systems and electronic equipment, and achieving efficient overvoltage protection.
Patent Information
- Application Number
- CN202610779235.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-06-30
AI Technical Summary
Zinc oxide varistors suffer from problems such as low density, uneven grain size, poor nonlinear characteristics, weak surge current carrying capacity, large leakage current, and poor performance stability and batch consistency, making them unsuitable for overvoltage protection requirements of medium and high voltage power systems and precision electronic equipment.
By optimizing the ingredient composition and preparation process, including rationally controlling the process parameters of mixing, molding, debinding and sintering, the density of zinc oxide varistors is ensured to be ≥95%, the grain size distribution is between 5 and 15 μm, the nonlinear coefficient α≥50, the surge current capacity is ≥20kA, the leakage current is ≤5 μA, and the absolute value of the voltage temperature coefficient αV, |αV|, is ≤0.05%/℃.
A zinc oxide varistor ceramic with excellent performance, strong stability, and good batch consistency was obtained. It can effectively suppress transient overvoltages, release surge energy, and ensure the safe and stable operation of medium and high voltage power systems and electronic equipment.
Smart Images

Figure SMS_3 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to the field of varistors ceramics, specifically to zinc oxide varistors ceramics, their preparation methods, and applications. Background Technology
[0002] Zinc oxide varistors are functional ceramics with nonlinear voltage-current characteristics. Their resistance decreases sharply with increasing applied voltage, enabling them to quickly conduct and release surge energy during transient overvoltage events, effectively protecting power systems and electronic equipment from overvoltage surges. Therefore, zinc oxide varistors are widely used in medium- and high-voltage power protection, overvoltage protection of electronic equipment, and lightning protection of communication equipment, making them a core material for overvoltage protection components.
[0003] Currently, zinc oxide varistors generally suffer from problems such as low density, uneven grain size, poor nonlinear characteristics, weak surge current carrying capacity, large leakage current, and poor performance stability and batch consistency. These issues prevent them from fully fulfilling their core function of overvoltage protection, thereby affecting the operational safety and service life of related equipment. These defects make zinc oxide varistors unsuitable for medium- and high-voltage power systems, precision electronic equipment, and other applications with high performance requirements for varistors, thus limiting their application scope and effectiveness. Summary of the Invention
[0004] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a zinc oxide varistor ceramic, its preparation method, and its application. By rationally controlling the process parameters of each step, including batching, mixing, molding, debinding, sintering, and electrode preparation, the microstructure of the varistor ceramic is improved, enhancing its density, grain uniformity, and macroscopic electrical properties. This results in a zinc oxide varistor ceramic with excellent performance, strong stability, and good batch-to-batch consistency, capable of meeting the practical needs of medium- and high-voltage protection scenarios.
[0005] In view of the above, a first aspect of the present invention provides a zinc oxide varistor ceramic comprising the following raw materials: 90.3-95.4 wt% zinc oxide, 2-4 wt% bismuth oxide, 1.5-2.5 wt% antimony oxide, 0.5-1.5 wt% cobalt oxide, 0.3-0.8 wt% manganese oxide, 0.2-0.6 wt% silicon oxide, and 0.1-0.3 wt% aluminum oxide; The zinc oxide varistor ceramic has a density of ≥95% and a grain size distribution between 5 and 15 μm.
[0006] Therefore, zinc oxide, as the matrix material, provides the basic structure and nonlinear characteristics of the ceramic; bismuth oxide and antimony oxide, as main dopants, form grain boundary layers, which can regulate grain growth and improve the nonlinear coefficient and voltage stability of the ceramic; cobalt oxide and manganese oxide, as auxiliary dopants, refine the grains, which can improve the surge current carrying capacity and density of the ceramic; silicon oxide and aluminum oxide optimize the grain boundary structure, which can reduce leakage current and improve the performance stability and high-temperature resistance of the ceramic. The various raw materials work synergistically to ensure the excellent and stable performance of the zinc oxide varistor ceramic.
[0007] The zinc oxide varistor ceramic of this invention has high density, uniform grains, and excellent performance in various aspects, including high nonlinear coefficient, strong surge current carrying capacity, low leakage current, and stable performance. It can be widely used in overvoltage protection in medium and high voltage power systems, electronic equipment, communication equipment, and other fields. It can effectively suppress transient overvoltages, release surge energy, and ensure the safe and stable operation of related equipment, thus solving the problem that related varistor ceramics are difficult to adapt to medium and high voltage protection scenarios.
[0008] According to embodiments of the present invention, the above-mentioned zinc oxide varistor ceramic may further include at least one of the following additional technical features: In some embodiments, the nonlinear coefficient α of the zinc oxide varistor is ≥50.
[0009] In some embodiments, the surge current carrying capacity of the zinc oxide varistor is ≥20kA.
[0010] In some embodiments, the leakage current of the zinc oxide varistor is ≤ 5 μA.
[0011] In some embodiments, the voltage temperature coefficient α of the zinc oxide varistor ceramic in the temperature range of -40°C to 85°C V absolute value | α V | ≤ 0.05 % / ℃.
[0012] In some embodiments, the particle size of the raw material is ≤10 μm.
[0013] A second aspect of the present invention provides a method for preparing the aforementioned zinc oxide varistor ceramic, comprising: The raw materials are mixed with water and dispersant, and then ball-milled to obtain a slurry; The slurry is dried and granulated to obtain granulated particles; The particles are pressed into shape to obtain a green body; The green body is then subjected to debinding treatment; The debinding green body is sintered to obtain the zinc oxide varistor ceramic; The sintering includes a first sintering and a second sintering performed sequentially. The first sintering includes: heating to 600-700℃ at a heating rate of 3-5℃ / min and holding at that temperature for 1-1.5 h; The second sintering process includes heating to 1150-1250 ℃ at a heating rate of 2-3 ℃ / min and holding at that temperature for 3-5 h.
[0014] This facilitates the coordination and synergy between each step, ultimately resulting in ceramic materials with high density, uniform grain distribution, and excellent nonlinear characteristics, meeting the application requirements of medium- and high-voltage overvoltage protection scenarios. Ball milling ensures thorough and uniform mixing of raw materials, granulation and molding to obtain green bodies with uniform density, and complete removal of organic matter through debinding. Two-stage sintering precisely controls grain growth and densification. By controlling the heating rate, sintering temperature, holding time, and cooling rate during sintering in stages, uniform distribution of ceramic grains can be achieved, avoiding excessive or uneven grain growth, forming a regular and dense microstructure, thereby improving the density, surge current carrying capacity, and voltage stability of the ceramic. This invention features a simple process, strong operability, and is suitable for industrial production. It has low production costs, a short production cycle, and good batch consistency, making it suitable for large-scale application.
[0015] According to embodiments of the present invention, the above method may further include at least one of the following additional technical features: In some embodiments, the mass ratio of the raw material, deionized water, and dispersant is 100:(30~40):(0.5~1.0).
[0016] In some embodiments, the ball mill rotation speed is 300~400 r / min, and the ball milling time is 6~8 h.
[0017] In some embodiments, the dispersant includes at least one of polyethylene glycol or sodium citrate.
[0018] In some embodiments, the ball-to-material ratio of the ball mill is 5:1 to 8:1.
[0019] In some embodiments, the inlet temperature of the drying granulation is 180~200 ℃, and the outlet temperature is 80~100 ℃.
[0020] In some embodiments, the drying granulation includes spray drying.
[0021] Furthermore, the atomization pressure of the spray drying is 0.3~0.5 MPa.
[0022] In some embodiments, the particle size of the granulated particles is 80~120 μm.
[0023] In some embodiments, the drying and granulation equipment includes a spray dryer.
[0024] In some embodiments, the molding pressure of the compression molding is 15~25 MPa, and the holding time is 30~60 s.
[0025] In some embodiments, the compression molding equipment includes a hydraulic molding machine.
[0026] In some embodiments, the density of the green body is ≥2.8 g / cm³. 3 .
[0027] In some embodiments, the debinding process includes heating to 450-550°C at a heating rate of 5-8°C / min, holding at that temperature for 2-3 hours, and then cooling to room temperature at a cooling rate of 3-5°C / min.
[0028] A third aspect of the present invention provides a varistor comprising the aforementioned zinc oxide varistor ceramic or zinc oxide varistor ceramic prepared by the aforementioned method, and electrodes disposed on both ends of the zinc oxide varistor ceramic. Thus, this varistor possesses all the features and advantages of the zinc oxide varistor ceramic or its preparation method, which will not be elaborated further here.
[0029] In some embodiments, the electrode is formed by vacuum sputtering.
[0030] Furthermore, the vacuum sputtering power is 100~150 W, the vacuum sputtering time is 10~20 min, and the vacuum sputtering pressure is 0.1~0.3 Pa.
[0031] In some embodiments, the electrode further includes an annealing process after deposition.
[0032] Furthermore, the annealing temperature of the annealing treatment is 300~350 ℃, and the holding time of the annealing treatment is 1~1.5 h.
[0033] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0034] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0035] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0036] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0037] In this document, the terms “comprising” or “including” are open-ended expressions, meaning they include the contents specified in this invention but do not exclude other aspects.
[0038] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.
[0039] This application is based on the inventor's following discoveries and understandings: The performance of zinc oxide varistors (especially nonlinear coefficient, surge current carrying capacity, leakage current, and voltage stability) depends not only on the raw material formulation but also significantly on the preparation process. Process parameters such as batching accuracy, mixing uniformity, molding pressure, binder removal regime, sintering temperature, and holding time directly determine the ceramic's microstructure (e.g., density, grain size and distribution, grain boundary characteristics), which in turn directly relates to its macroscopic electrical properties. Therefore, optimizing the preparation process is crucial for improving the performance of zinc oxide varistors.
[0040] The inventors discovered that the preparation process of the relevant zinc oxide varistors has many flaws, making it difficult for their performance to meet the requirements of demanding applications such as medium and high voltage. Specifically, these flaws are manifested in the following aspects: (1) Imperfect mixing process: Most related technologies use simple dry grinding or short-time wet grinding, resulting in uneven mixing of raw materials. Dopants (such as bismuth oxide, antimony oxide, etc.) are difficult to disperse evenly in the zinc oxide matrix, leading to uneven grain growth and irregular grain boundary structure during subsequent sintering, which in turn reduces the nonlinear coefficient, increases leakage current, and affects protection accuracy.
[0041] (2) Unreasonable molding process parameters: Too low molding pressure will result in insufficient density of the green body, more internal pores, and difficulty in forming dense ceramics after sintering, which will easily lead to cracking and breakage; too high molding pressure will lead to stress concentration inside the green body, which will easily cause deformation during glue removal and sintering, affecting the stability of ceramic performance. At the same time, the control of holding time in related molding processes is relatively rough, which further aggravates the problem of uneven density of green bodies.
[0042] (3) Inadequate control of sintering process: Unreasonable setting of parameters such as sintering temperature, heating rate, and holding time are the core factors affecting the performance of varistors. Too rapid heating rate will cause the moisture and organic matter inside the green body to evaporate quickly, resulting in stress cracking; too low sintering temperature will lead to insufficient sintering, low ceramic density, and small and uneven grains; too high sintering temperature or too long holding time will lead to excessive grain growth and uneven grain boundary thickness, reducing surge current carrying capacity and voltage stability. In addition, some processes fail to control the sintering atmosphere, leading to oxidation of the ceramic surface and further deterioration of performance.
[0043] (4) Imperfect debinding process: The debinding process is a key step in removing moisture and organic matter from the green body. If the heating rate is too fast or the holding time is insufficient, the organic matter will not be fully decomposed and volatilized. The residual organic matter will generate gas during sintering, forming pores, reducing the density of the ceramic, and affecting the grain boundary reaction, resulting in poor batch-to-batch consistency of ceramic performance.
[0044] (5) The electrode preparation process is rudimentary: The electrode preparation process mainly adopts the method of applying silver paste and then drying. The bonding force between the electrode and the varistor ceramic is weak. During long-term use, the electrode is prone to detachment and poor contact, which affects the conductivity and protective function of the varistor ceramic. At the same time, no annealing treatment is performed during the electrode preparation process, which further reduces the stability of the electrode bonding.
[0045] Therefore, it is necessary to study and optimize the preparation process of zinc oxide varistors. By rationally controlling the process parameters of each step, such as batching, mixing, molding, debinding, sintering and electrode preparation, the microstructure of the ceramic can be improved, and its density, grain uniformity and macroscopic electrical properties can be enhanced. In this way, zinc oxide varistors with excellent performance, strong stability and good batch consistency can be obtained to meet the actual needs of medium and high voltage protection scenarios.
[0046] Based on the above research, the inventors developed a new zinc oxide varistor ceramic and its preparation method. By rationally controlling the process parameters of each step, such as batching, mixing, molding, debinding, sintering and electrode preparation, the microstructure of the varistor ceramic was improved, and its density, grain uniformity and macroscopic electrical properties were enhanced. This resulted in a zinc oxide varistor ceramic with excellent performance, strong stability and good batch consistency, which can meet the actual needs of medium and high voltage protection scenarios.
[0047] In view of the above, a first aspect of the present invention provides a zinc oxide varistor ceramic comprising the following raw materials: 90.3-95.4 wt% zinc oxide, 2-4 wt% bismuth oxide, 1.5-2.5 wt% antimony oxide, 0.5-1.5 wt% cobalt oxide, 0.3-0.8 wt% manganese oxide, 0.2-0.6 wt% silicon oxide, and 0.1-0.3 wt% aluminum oxide; The zinc oxide varistor ceramic has a density of ≥95% and a grain size distribution between 5 and 15 μm.
[0048] Therefore, zinc oxide, as the matrix material, provides the basic structure and nonlinear characteristics of the ceramic; bismuth oxide and antimony oxide, as main dopants, form grain boundary layers, which can regulate grain growth and improve the nonlinear coefficient and voltage stability of the ceramic; cobalt oxide and manganese oxide, as auxiliary dopants, refine the grains, which can improve the surge current carrying capacity and density of the ceramic; silicon oxide and aluminum oxide optimize the grain boundary structure, which can reduce leakage current and improve the performance stability and high-temperature resistance of the ceramic. The various raw materials work synergistically to ensure the excellent and stable performance of the zinc oxide varistor ceramic.
[0049] The zinc oxide varistor ceramic of this invention has high density, uniform grains, and excellent performance in various aspects, including high nonlinear coefficient, strong surge current carrying capacity, low leakage current, and stable performance. It can be widely used in overvoltage protection in medium and high voltage power systems, electronic equipment, communication equipment, and other fields. It can effectively suppress transient overvoltages, release surge energy, and ensure the safe and stable operation of related equipment, thus solving the problem that related varistor ceramics are difficult to adapt to medium and high voltage protection scenarios.
[0050] Controlling the density within the aforementioned range helps reduce porosity defects inside the ceramic, forming a continuous and dense grain boundary structure, thereby reducing leakage current channels and positively impacting the nonlinear coefficient and surge withstand capability. If the density is too low, there will be more pores, which can easily become leakage current paths, leading to deterioration of nonlinear characteristics and a decrease in current carrying capacity.
[0051] Controlling the grain size within the aforementioned range helps to form a regular and moderately thick grain boundary layer, allowing each grain boundary to respond synergistically under the influence of an electric field, thereby achieving a higher nonlinear coefficient and stable voltage clamping performance. If the grain size is too large, the number of grain boundaries per unit thickness will decrease, which may reduce nonlinear characteristics and make surge energy absorption capacity insufficient; if the grain size is too small, it may lead to an increase in grain boundary defects, an increase in leakage current, and a decrease in voltage and temperature stability.
[0052] For example, the mass percentage of each component in the raw material can be independently specified as follows: the content of zinc oxide can be 90.3 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 95.4 wt%, etc.; the content of bismuth oxide can be 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, etc.; the content of antimony oxide can be 1.5 wt%, 1.8 wt%, 2 wt%, 2.2 wt%, 2.5 wt%, etc.; the content of cobalt oxide can be 0.5 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.5 wt%, etc.; the content of manganese oxide can be 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, etc.; and the content of silicon oxide can be 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, etc. The alumina content can be 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, etc.
[0053] For example, the density of the zinc oxide varistor ceramic can be 95%, 96%, 97%, 98%, 99%, etc. The grain size can be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, etc.
[0054] Preferably, the grain size is uniformly distributed between 5 and 15 μm.
[0055] Uniform grain distribution facilitates synchronized responses at each grain boundary under an electric field, forming a coordinated overall barrier structure. This significantly improves the nonlinear coefficient and reduces the risk of thermal failure caused by localized current concentration. If the grain size distribution is uneven (a mixture of excessively large and small grains), the grain boundary barrier heights become inconsistent, and leakage current may preferentially flow through the smaller grain regions, degrading the nonlinear characteristics. Simultaneously, the larger grain regions may experience excessively high electric fields, leading to a decrease in surge current carrying capacity and difficulty in ensuring voltage and temperature stability.
[0056] In some embodiments, the nonlinear coefficient α of the zinc oxide varistor is ≥50, specifically 50, 55, 60, 65, 70, etc. An α value within this range facilitates a rapid response of the varistor when overvoltage occurs, achieving a steep voltage-current characteristic transition, thereby accurately clamping the circuit voltage and reducing the risk of damage to the protected equipment. If the α value is too low, the voltage-current characteristic transition is gentle, resulting in insufficient surge absorption capacity and making it difficult to meet the voltage clamping accuracy requirements of medium- and high-voltage protection scenarios.
[0057] In some embodiments, the surge current carrying capacity of the zinc oxide varistor is ≥20kA, specifically, it can be 20kA, 25kA, 30kA, 35kA, 40kA, etc. Within this range, the varistor is better able to absorb sufficient surge energy when subjected to lightning strikes or operational overvoltages, avoiding thermal breakdown or mechanical damage, thereby improving the survival probability of the equipment. If the current carrying capacity is too low, it will be difficult to withstand the large current impact in medium and high voltage systems, and may fail prematurely, losing its overvoltage protection function.
[0058] It should be noted that the "surge current carrying capacity" mentioned in this invention refers to the single peak surge current value that the varistor ceramic can withstand under an 8 / 20μs standard current waveform (wavefront time 8μs, half-peak time 20μs). The test method refers to the standard GB / T 17626.5-2019 "Electromagnetic compatibility testing and measurement techniques - surge (impulse) immunity test".
[0059] In some embodiments, the leakage current of the zinc oxide varistor is ≤ 5 μA, specifically 0.5 μA, 1 μA, 2 μA, 3 μA, 4 μA, 5 μA, etc. A leakage current within this range helps reduce Joule heat loss in the varistor during continuous operation, slows down the thermal degradation rate of the grain boundary barrier, thereby extending its service life and maintaining stable nonlinear characteristics. If the leakage current is too high, the grain boundaries may gradually deteriorate due to localized overheating during long-term operation, easily leading to a decrease in the nonlinear coefficient or even thermal collapse.
[0060] It should be noted that the leakage current described in this invention is obtained by applying the nominal varistor voltage (i.e., rated voltage) to the varistor ceramic at room temperature (25℃±2℃), stabilizing for 30 seconds, and then reading the current value.
[0061] In some embodiments, the voltage temperature coefficient α of the zinc oxide varistor ceramic in the temperature range of -40°C to 85°C V absolute value | α V | ≤ 0.05 % / ℃. For example, the voltage temperature coefficient α V absolute value | α V | It can be 0.05 % / ℃, 0.03 % / ℃, 0.02 % / ℃, 0.01 % / ℃, 0 % / ℃, etc.
[0062] This helps the varistor maintain a stable voltage clamping value in extremely cold or high-temperature environments, reducing malfunctions or protection failures caused by temperature drift, making it particularly suitable for outdoor power equipment and vehicle electronic systems. If the absolute value of the voltage temperature coefficient is too large, the varistor voltage may be too low at high temperatures, causing premature conduction, or too high at low temperatures, leading to an increase in residual voltage and reduced reliability.
[0063] It should be noted that the voltage temperature coefficient mentioned in this invention is calculated by placing the varistor ceramic in a programmable temperature chamber and measuring the varistor voltage at -40 ℃, 25 ℃, and 85 ℃ (using the voltage value under 1 mA DC current as the varistor voltage). The voltage temperature coefficient α is... V The calculation formula is: , where V 85 V 40 V 25 These represent the varistor voltages at the corresponding temperatures.
[0064] In some embodiments, the purity of the raw material is ≥99.5%, specifically such as 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, etc.
[0065] This ensures the high activity of raw materials and prevents impurity elements (such as alkali metals and iron) from segregating at grain boundaries or forming harmful second phases, thereby maintaining a regular grain boundary barrier structure, effectively reducing leakage current, and improving the stability of nonlinear coefficient and surge current carrying capacity.
[0066] In some embodiments, the particle size of the raw material is ≤10 μm, specifically such as 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, etc.
[0067] Within the aforementioned particle size range, it is beneficial for the components to be fully dispersed during wet milling, promoting the uniform distribution of dopants in the zinc oxide matrix. This provides a good foundation for the formation of a regular and dense grain boundary structure during subsequent sintering, and is advantageous for improving surge current capacity and batch consistency. If the particle size is too high, the solid-phase reaction between raw materials may be uneven, easily inducing abnormal local grain growth, thereby reducing the density and nonlinear characteristics of the ceramic. If the particle size is too low, the tendency for powder agglomeration is enhanced, which may adversely affect mixing and molding, making it difficult to ensure the consistency of the microstructure.
[0068] A second aspect of the present invention provides a method for preparing the aforementioned zinc oxide varistor ceramic, comprising: The raw materials are mixed with water and dispersant, and then ball-milled to obtain a slurry; The slurry is dried and granulated to obtain granulated particles; The particles are pressed into shape to obtain a green body; The green body is then subjected to debinding treatment; The debinding green body is sintered to obtain the zinc oxide varistor ceramic; The sintering includes a first sintering and a second sintering performed sequentially. The first sintering includes: heating to 600-700℃ at a heating rate of 3-5℃ / min and holding at that temperature for 1-1.5 h; The second sintering process includes heating to 1150-1250 ℃ at a heating rate of 2-3 ℃ / min and holding at that temperature for 3-5 h.
[0069] This facilitates the coordination and synergy between each step, ultimately resulting in ceramic materials with high density, uniform grain distribution, and excellent nonlinear characteristics, meeting the application requirements of medium- and high-voltage overvoltage protection scenarios. Ball milling ensures thorough and uniform mixing of raw materials, granulation and molding to obtain green bodies with uniform density, complete removal of organic matter through debinding, and precise control of grain growth and densification processes through two-stage sintering. This invention features a simple process, strong operability, and ease of industrial production. It requires no complex equipment or demanding production conditions; the process parameters for each step are clear and easily controlled; production costs are low; and the production cycle is short with good batch consistency, enabling industrial-scale mass production and suitable for large-scale application.
[0070] By controlling the heating rate, sintering temperature, holding time, and cooling rate during sintering in stages, it is possible to achieve uniform grain distribution in ceramics, avoiding excessive or uneven grain growth, and forming a regular and dense microstructure. This, in turn, improves the density, surge current carrying capacity, and voltage stability of the ceramic. Therefore, the sintering process is the core factor affecting the microstructure of ceramics. Reasonable sintering parameters can ensure uniform grain growth and stable grain boundary structure, significantly improving the macroscopic properties of ceramics.
[0071] Within the aforementioned range, the heating rate during the first sintering stage is beneficial for the green body to heat up slowly during the low-temperature pre-sintering phase. This avoids the violent vaporization of internal moisture and residual organic matter caused by a sudden temperature rise, thereby reducing the risk of cracking. It also lays the foundation for a uniform temperature field in the subsequent high-temperature sintering. If the heating rate is too high, significant thermal stress may be generated inside the green body, easily leading to cracks or delamination defects. If the heating rate is too low, the production cycle will be prolonged, energy consumption will increase, and economic efficiency will decrease.
[0072] The holding temperature for the first sintering is within the above-mentioned range, which is beneficial for the complete decomposition and volatilization of residual organic matter in the varistor ceramic and promotes the initial reaction of each component to form a uniform intermediate phase, thereby improving the uniformity of the grain boundary structure. If the temperature is too high, some dopants may volatilize excessively or form phase structures that are not conducive to subsequent sintering in advance; if the holding temperature is too low, the organic matter will not decompose completely, and the residual carbides may generate pores during high-temperature sintering, resulting in low ceramic density, fine and uneven grains, and poor nonlinear coefficient and surge current carrying capacity.
[0073] Within the aforementioned range, the holding time for the first sintering stage helps ensure uniform internal temperature of the pressure-sensitive ceramic and allows for sufficient removal of organic matter, while avoiding excessive energy consumption. If the holding time is too long, although the binder removal is more thorough, it may cause some grains to grow prematurely and reduce production efficiency; if the holding time is too short, insufficient binder removal may lead to porosity defects during subsequent sintering.
[0074] Within the aforementioned range, the heating rate during the second sintering stage is beneficial for the smooth transition of the varistor ceramic from the pre-sintering temperature to the high-temperature sintering stage, preventing runaway grain growth due to excessively rapid heating and thus ensuring the uniformity of grain size. If the heating rate is too high, the grains may grow abnormally, resulting in a wider grain size distribution and a decrease in the nonlinear coefficient; if the heating rate is too low, the sintering cycle will be significantly prolonged, which is not conducive to industrial mass production.
[0075] The holding temperature for the second sintering is within the above-mentioned range, which is conducive to activating grain boundary migration and densification processes, allowing grains to grow fully and be closely packed, thereby obtaining grains with high density and suitable size. If the holding temperature is too high, the grains may grow excessively, resulting in a reduction in the number of grain boundaries per unit thickness, and a significant decrease in surge current carrying capacity and nonlinear coefficient; if the holding temperature is too low, sintering will be insufficient, leaving more pores, making it difficult to achieve the required density, and leakage current will easily increase.
[0076] Within the aforementioned range, the holding time for the second sintering stage allows for sufficient grain growth and the achievement of a stable grain boundary structure, while avoiding over-sintering. If the holding time is too long, excessive grain growth can occur, leading to grain coarsening, uneven grain boundary thickness, and decreased voltage and temperature stability. Conversely, if the holding time is too short, insufficient sintering and incomplete grain growth result in porosity within the ceramic, insufficient density, and reduced surge current carrying capacity.
[0077] For example, the heating rate of the first sintering can be 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min, etc.; the holding temperature of the first sintering can be 600℃, 630℃, 650℃, 680℃, 700℃, etc.; the holding time of the first sintering can be 1h, 1.2h, 1.3h, 1.4h, 1.5h, etc.; the heating rate of the second sintering can be 2℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min, 3℃ / min, etc.; the holding temperature of the second sintering can be 1150℃, 1180℃, 1200℃, 1220℃, 1250℃, etc.; the holding time of the second sintering can be 3h, 3.5h, 4h, 4.5h, 5h, etc.
[0078] In some embodiments, the mass ratio of the raw materials, deionized water, and dispersant is 100:(30~40):(0.5~1.0), specifically such as 100:30:0.5, 100:30:0.8, 100:30:0.1, 100:35:0.5, 100:35:0.8, 100:35:0.1, 100:40:0.5, 100:40:0.8, 100:40:1.0, etc.
[0079] This facilitates the formation of a slurry with moderate solid content and good fluidity, ensuring sufficient dispersion and uniform collision of raw material particles during ball milling, thereby improving mixing efficiency. If the water ratio is too high, the slurry viscosity is too low, resulting in decreased grinding efficiency, insufficient particle refinement, and uneven mixing of raw materials. Conversely, if the water ratio is too low, the slurry becomes too thick, reducing fluidity and hindering contact between the grinding media and the raw materials, also negatively impacting uniform mixing. Dispersants prevent particle agglomeration, further enhancing mixing uniformity and ensuring uniform dispersion of dopants within the zinc oxide matrix, laying the foundation for the subsequent formation of a uniform microstructure. If the dispersant ratio is too high, excessive organic residue may be introduced, easily leading to porosity during debinding; if the dispersant ratio is too low, particle agglomeration is likely, making it difficult to guarantee uniform mixing of the raw materials.
[0080] In some embodiments, the ball mill rotation speed is 300-400 r / min, and the ball milling time is 6-8 h. Specifically, the ball mill rotation speed can be 300 r / min, 330 r / min, 350 r / min, 380 r / min, 400 r / min, etc.; and the ball milling time can be 6 h, 6.5 h, 7 h, 7.5 h, 8 h, etc.
[0081] This allows the raw material particles to receive sufficient impact and shear energy, achieving uniform dispersion of all components, especially trace dopants. This provides a good foundation for the formation of a uniform grain boundary structure during subsequent sintering, avoiding problems such as uneven grain growth and irregular grain boundaries caused by uneven mixing in related technologies. This, in turn, improves the nonlinear coefficient of the ceramic, reduces leakage current, and enhances the ceramic's protective precision. The uniformity of mixing directly affects the grain boundary reaction during subsequent sintering. The more uniform the mixing, the more regular the grain boundary structure, and the better the nonlinear characteristics and stability of the ceramic. If the rotation speed is too low or the time is too short, the raw materials will be mixed unevenly and cannot be fully dispersed, leading to uneven grain growth, grain boundary segregation, and a decrease in nonlinear coefficient and surge current capacity after sintering. If the rotation speed is too high or the time is too long, the raw material particles will become excessively fine, easily leading to poor particle flowability during drying and granulation, increasing the difficulty of drying and granulation, and potentially introducing impurities.
[0082] In some embodiments, the dispersant includes at least one of polyethylene glycol or sodium citrate.
[0083] In some embodiments, the ball-to-material ratio in the ball milling process is 5:1 to 8:1, specifically 5:1, 6:1, 7:1, 8:1, etc. Within this range, it is beneficial to achieve a balance between grinding efficiency and slurry quality, avoiding over-refinement or the introduction of impurities. If the ball-to-material ratio is too high, over-grinding may occur, resulting in excessively fine particles that easily introduce impurities and excessively high slurry viscosity; if the ball-to-material ratio is too low, it may lead to uneven dispersion of dopants, resulting in reduced grain boundary regularity and nonlinear coefficient after sintering.
[0084] In some embodiments, the grinding balls used in the ball mill are zirconia balls. Zirconia balls have high hardness, good wear resistance, and do not introduce impurities, thus ensuring grinding effectiveness.
[0085] Furthermore, the grinding balls have a particle size of 10-30 mm, specifically 10 mm, 20 mm, 25 mm, 30 mm, etc. This facilitates the provision of moderate impact energy during the grinding process, effectively refining the raw material particles without excessive breakage, while maintaining good mixing uniformity. If the particle size is too large, the impact energy will be too strong, potentially damaging the raw material particle structure or introducing more impurities; if the particle size is too small, the dopant may be difficult to disperse sufficiently, easily leading to a decrease in grain boundary uniformity and a reduction in the nonlinear coefficient after sintering.
[0086] In some embodiments, the ball milling apparatus includes a planetary ball mill.
[0087] In some embodiments, the inlet temperature of the drying granulation process is 180~200℃, and the outlet temperature is 80~100℃. For example, the inlet temperature of the drying granulation process can be 180℃, 185℃, 190℃, 195℃, 200℃, etc.; and the outlet temperature can be 80℃, 85℃, 90℃, 95℃, 100℃, etc.
[0088] Within the aforementioned temperature range, the inlet temperature facilitates proper evaporation of moisture from the slurry, resulting in smooth-surfaced and internally dry granules. This also prevents overheating or insufficient drying, ensuring granule flowability and uniformity. If the inlet temperature is too low, insufficient slurry drying can lead to granule agglomeration. If the inlet temperature is too high, the granule surface may scorch or harden, affecting subsequent pressing during molding. Within the aforementioned outlet temperature range, the temperature helps ensure sufficient moisture escapes from the granules, while also mitigating the risks associated with insufficient slurry drying, granule agglomeration or adhesion, and reduced flowability. Conversely, if the inlet temperature is too high, the granule surface may scorch or harden, affecting subsequent pressing during molding.
[0089] Maintaining the outlet temperature within the above range allows for sufficient evaporation of moisture from the granules, while preventing cracking due to sudden cooling. If the outlet temperature is too high, the granules may harden on the surface or develop microcracks due to excessive water loss, affecting molding performance. If the outlet temperature is too low, incomplete drying will result in high residual moisture content in the granules, making them prone to porosity during subsequent glue removal.
[0090] In some embodiments, the drying granulation includes spray drying.
[0091] Furthermore, the atomization pressure of the spray drying is 0.3~0.5 MPa, specifically such as 0.30 MPa, 0.32 MPa, 0.35 MPa, 0.38 MPa, 0.40 MPa, 0.42 MPa, 0.45 MPa, 0.48 MPa, and 0.50 MPa. Atomization pressure within this range is beneficial for dispersing the slurry into uniform and fine droplets, thereby obtaining particles with concentrated particle size distribution and good flowability, facilitating subsequent molding and ensuring uniform green body density. If the atomization pressure is too low, the droplet size may be too large and widely distributed, resulting in uneven particle size after drying and causing differences in green body density; if the atomization pressure is too high, the droplets may be too fine, resulting in excessively small particles after drying, increased dust, and hindering the molding operation.
[0092] In some embodiments, the particle size of the granulated particles is 80~120 μm, specifically 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, etc. This facilitates close packing during molding, resulting in uniform density throughout the green body and reducing deformation or cracks caused by uneven sintering shrinkage. If the particle size is too large or too small, it will lead to uneven particle packing during molding, resulting in large differences in green body density, which in turn reduces the density and performance consistency of the sintered ceramic.
[0093] In some embodiments, the drying and granulation equipment includes a spray dryer.
[0094] In some embodiments, the molding pressure of the compression molding is 15~25 MPa, and the holding time is 30~60 s. For example, the molding pressure of the compression molding can be 15 MPa, 18 MPa, 20 MPa, 22 MPa, 25 MPa, etc., and the holding time can be 30 s, 40 s, 45 s, 50 s, 60 s, etc.
[0095] Molding pressure and holding time are core parameters affecting the density of green bodies. Precise control of these parameters helps improve green body density, reduce internal porosity, and enhance density uniformity, avoiding problems such as cracking, deformation, and uneven density caused by excessively high or low molding pressure. If the pressure is too low, the green body will have many internal pores and insufficient density, making it difficult to form a dense ceramic during subsequent sintering and increasing the likelihood of cracking. If the pressure is too high, stress concentration may occur within the green body, leading to deformation and cracking during binder removal and sintering. Holding time within the specified range ensures that pressure is evenly distributed throughout the green body, resulting in uniform density and preventing excessive local porosity, thus laying a good foundation for subsequent sintering. If the holding time is too short, pressure may not be sufficiently transmitted, leading to uneven green body density; if the holding time is too long, the improvement in density is limited, and it may even reduce production efficiency.
[0096] In some embodiments, the compression molding equipment includes a hydraulic molding machine.
[0097] In some embodiments, the density of the green body is ≥2.8 g / cm³, specifically 2.8 g / cm³, 2.9 g / cm³, 3.0 g / cm³, 3.1 g / cm³, 3.2 g / cm³, etc. Using the above-mentioned green body density is beneficial for improving the ceramic density and reducing deformation or cracking caused by uneven shrinkage of the green body. If the green body density is too low, there will be more internal pores, and the pores will be difficult to completely eliminate after sintering, which may result in insufficient ceramic density, thereby reducing the nonlinear coefficient and surge current capacity.
[0098] In some embodiments, the adhesive removal includes heating to 450-550°C at a heating rate of 5-8°C / min, holding at that temperature for 2-3 hours, and then cooling to room temperature at a cooling rate of 3-5°C / min. For example, the heating rate for adhesive removal can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc.; the holding temperature for adhesive removal can be 450°C, 480°C, 500°C, 520°C, 550°C, etc.; the holding time for adhesive removal can be 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours, etc.; and the cooling rate for adhesive removal can be 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, etc.
[0099] This avoids cracking of the green body and the retention of organic matter, effectively removing moisture and organic matter from the green body. Specifically: Within the above-mentioned heating rate range, it is beneficial for the steady evaporation of moisture and organic matter in the green body, reducing internal stress caused by rapid gas escape and thus lowering the risk of cracking. If the heating rate is too fast, the moisture and organic matter will evaporate quickly, easily generating stress inside the green body and leading to cracking; if the heating rate is too slow, it will prolong the production cycle and increase production costs.
[0100] Maintaining the holding temperature within the above range is beneficial for the complete decomposition and volatilization of organic matter, preventing residual carbides from forming pores during subsequent sintering. If the holding temperature is too high, some dopants may volatilize prematurely or undergo unfavorable pre-reactions, affecting the grain boundary composition; if the holding temperature is too low, the organic matter will not decompose completely, and the residues are prone to generating gas during the high-temperature sintering stage, leading to an increase in the internal porosity of the ceramic.
[0101] Within the above-mentioned holding time range, organic residue can be avoided while preventing excessive energy consumption. If the holding time is too long, although the binder removal is more thorough, it may increase energy consumption and has no significant additional benefit to the microstructure of the green body; if the holding time is too short, insufficient binder removal may lead to a decrease in the density of the ceramic after sintering and an increase in leakage current.
[0102] The cooling rate within the aforementioned range is beneficial for releasing internal stress in the green body, preventing cracking due to sudden cooling, and avoiding problems such as gas generation, porosity formation, and reduced ceramic density caused by residual organic matter during sintering, as well as affecting grain boundary structure and deteriorating ceramic properties. If the cooling rate is too high, the green body may develop latent cracks due to thermal shock, affecting the yield of subsequent sintering; if the cooling rate is too low, the cooling time will be too long, which is detrimental to production efficiency.
[0103] In some embodiments, the sintering atmosphere is air. This allows for complete oxidation of the raw materials without the need for additional protective gas, which helps reduce production costs and facilitates industrial production.
[0104] In some embodiments, the sintering equipment is a sintering furnace.
[0105] Furthermore, the oxygen content in the sintering furnace is 20-21%, specifically 20%, 20.2%, 20.5%, 20.8%, 21%, etc. This helps ensure sufficient oxidation of the raw materials, forming a regular grain boundary structure and avoiding the deterioration of ceramic properties caused by oxygen deficiency.
[0106] In some embodiments, before mixing, the raw materials are weighed using an electronic balance with a weighing accuracy of ≤ ±0.1g. For example, the weighing accuracy can be ±0.01g, ±0.03g, ±0.05g, ±0.08g, ±0.1g, etc. This ensures accurate proportioning and avoids ratio deviations affecting ceramic performance. Insufficient proportioning accuracy can lead to deviations in dopant content, which in turn affects grain boundary reactions and grain growth, reducing the nonlinear characteristics and stability of the ceramic.
[0107] A third aspect of the present invention provides a varistor comprising the aforementioned zinc oxide varistor ceramic or zinc oxide varistor ceramic prepared by the aforementioned method, and electrodes disposed on both ends of the zinc oxide varistor ceramic. Thus, this varistor possesses all the features and advantages of the zinc oxide varistor ceramic or its preparation method, which will not be elaborated further here.
[0108] In some embodiments, the electrode is a silver electrode.
[0109] In some embodiments, the electrode is formed by vacuum sputtering. Compared with traditional silver paste coating, vacuum sputtering results in a more uniform electrode thickness and stronger adhesion, solving the problems of weak adhesion and easy detachment of existing electrodes. It also improves the adhesion between the electrode and the ceramic substrate, ensuring stable conductivity of the varistor ceramic during long-term use and preventing poor electrode contact from affecting its protective function.
[0110] Furthermore, the vacuum sputtering power is 100~150 W, the vacuum sputtering time is 10~20 min, and the vacuum sputtering pressure is 0.1~0.3 Pa. For example, the vacuum sputtering power can be 100 W, 110 W, 120 W, 130 W, 140 W, 150 W, etc., the time can be 10 min, 12 min, 15 min, 18 min, 20 min, etc., and the pressure can be 0.1 Pa, 0.15 Pa, 0.2 Pa, 0.25 Pa, 0.3 Pa, etc.
[0111] This facilitates the formation of a uniform, dense, and well-adhered silver electrode layer on the ceramic substrate surface, thereby reducing contact resistance and improving electrode reliability. However, excessively high sputtering power may cause localized overheating on the ceramic surface, damaging the grain boundary structure and leading to a decrease in the nonlinear coefficient. Conversely, insufficient power results in a slow deposition rate, potentially causing a porous electrode layer with weak adhesion. Excessively long sputtering times can lead to an overly thick electrode layer and increased internal stress, potentially inducing microcracks. Conversely, excessively short sputtering times may result in an overly thin electrode layer and reduced conductivity. Furthermore, excessively high sputtering pressure increases the collision frequency of sputtered atoms during their journey, reducing their energy upon reaching the substrate and causing a loose film structure. Conversely, excessively low pressure makes it difficult to maintain plasma, potentially reducing deposition uniformity.
[0112] In some embodiments, the electrode further includes an annealing process after deposition.
[0113] Further, the annealing temperature is 300~350℃, and the holding time is 1~1.5 h. For example, the annealing temperature can be 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, etc.; and the holding time can be 1h, 1.2h, 1.3h, 1.4h, 1.5h, etc.
[0114] This eliminates stress between the electrode and the ceramic blank, further enhancing the bonding strength and improving the long-term stability of the conductivity of the varistor ceramic, ensuring its stable protective function. If the annealing temperature is too high or the holding time is too long, it may lead to excessive oxidation of the electrode layer or changes in the ceramic grain boundary structure, potentially decreasing the nonlinear coefficient. If the annealing temperature is too low or the holding time is too short, stress release will be insufficient, resulting in inadequate electrode bonding strength and making the electrode prone to detachment or poor contact during long-term use.
[0115] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0116] Example 1 A zinc oxide varistor ceramic comprises the following raw materials: 93 wt% zinc oxide, 3 wt% bismuth oxide, 2 wt% antimony oxide, 1 wt% cobalt oxide, 0.5 wt% manganese oxide, 0.3 wt% silicon oxide, and 0.2 wt% aluminum oxide; the purity of all raw materials is ≥99.5%, and the particle size is ≤10μm.
[0117] Its preparation method includes the following steps: (1) Ingredients: Weigh each raw material according to the above mass percentage using an electronic balance (weighing accuracy ±0.1g) and set aside; (2) Wet grinding and mixing: The raw materials after batching are put into a planetary ball mill, and deionized water and polyethylene glycol (dispersant) are added. The mass ratio of raw materials, deionized water and dispersant is 100:35:0.8, the ball-to-material ratio is 6:1, the grinding balls are zirconia balls (particle size 20mm), the ball milling speed is 350 r / min, and the ball milling time is 7 h to obtain a uniform slurry; (3) Drying and granulation: The slurry is placed in a spray dryer with an inlet temperature of 190 ℃, an outlet temperature of 90 ℃, and an atomization pressure of 0.4 MPa. After drying, particles with a particle size of about 100 μm are obtained. (4) Molding: The granules are placed in the molding mold and pressed by a hydraulic molding machine. The molding pressure is 20 MPa and the holding time is 45 s to obtain a green body with a density of 2.9 g / cm³. (5) Debinding: Place the green body into the debinding furnace, heat it to 500°C at a heating rate of 6°C / min, keep it at that temperature for 2.5h, and then cool it to room temperature at a cooling rate of 4°C / min to complete the debinding. (6) Sintering: The green body after debinding is placed in a sintering furnace and heated to 650 ℃ at a heating rate of 4 ℃ / min, held for 1.2 h, then heated to 1200 ℃ at a heating rate of 2.5 ℃ / min, held for 4 h. The sintering process is carried out in an air atmosphere (oxygen content 20.5%). Finally, the temperature is lowered to room temperature at a cooling rate of 5 ℃ / min to obtain zinc oxide varistors.
[0118] A varistor includes a zinc oxide varistor ceramic prepared in this embodiment, and electrodes disposed on both ends of the zinc oxide varistor ceramic.
[0119] The method for preparing the varistor includes: depositing silver electrodes on both ends of the varistor ceramic using a vacuum sputtering process, with a sputtering power of 120 W, a sputtering time of 15 min, and a sputtering pressure of 0.2 Pa; after the deposition is completed, the ceramic product is placed in an annealing furnace, heated to 320 ℃, held at that temperature for 1.2 h, and then allowed to cool naturally to room temperature to obtain the varistor.
[0120] Example 2 A zinc oxide varistor ceramic comprises the following raw materials: 90.3 wt% zinc oxide, 4 wt% bismuth oxide, 2.5 wt% antimony oxide, 1.5 wt% cobalt oxide, 0.8 wt% manganese oxide, 0.6 wt% silicon oxide, and 0.3 wt% aluminum oxide; the purity of all raw materials is ≥99.5%, and the particle size is ≤10 μm.
[0121] Its preparation method includes the following steps: (1) Ingredients: Weigh each raw material according to the above mass percentage using an electronic balance (weighing accuracy ±0.1g) and set aside; (2) Wet grinding and mixing: The raw materials after batching are put into a planetary ball mill, and deionized water and sodium citrate (dispersant) are added. The mass ratio of raw materials, deionized water and dispersant is 100:30:0.5, the ball-to-material ratio is 5:1, the grinding balls are zirconia balls (particle size 10mm), the ball milling speed is 300 r / min, and the ball milling time is 8h to obtain a uniform slurry; (3) Drying and granulation: The slurry is placed in a spray dryer with an inlet temperature of 180 ℃, an outlet temperature of 80 ℃, and an atomization pressure of 0.3 MPa. After drying, particles with a particle size of about 80 μm are obtained. (4) Molding: The granules are placed in the molding mold and pressed by a hydraulic molding machine. The molding pressure is 15 MPa and the holding time is 60s to obtain the green body with a density of 2.8 g / cm³. (5) Debinding: Place the green body into the debinding furnace, heat it to 450 ℃ at a heating rate of 5 ℃ / min, keep it at that temperature for 3 hours, and then cool it to room temperature at a cooling rate of 3 ℃ / min to complete the debinding. (6) Sintering: The green body after debinding is placed in a sintering furnace and heated to 600 ℃ at a heating rate of 3 ℃ / min, held for 1.5 h, then heated to 1150 ℃ at a heating rate of 2 ℃ / min, held for 5 h. The sintering process is carried out in an air atmosphere (oxygen content 20%). Finally, the temperature is lowered to room temperature at a cooling rate of 4 ℃ / min to obtain the zinc oxide varistor ceramic.
[0122] A varistor includes a zinc oxide varistor ceramic prepared in this embodiment, and electrodes disposed on both ends of the zinc oxide varistor ceramic.
[0123] The method for preparing the varistor includes: depositing silver electrodes on both ends of the varistor ceramic using a vacuum sputtering process, with a sputtering power of 100W, a sputtering time of 20 min, and a sputtering gas pressure of 0.1 Pa; after the deposition is completed, the ceramic product is placed in an annealing furnace, heated to 300 ℃, held at that temperature for 1.5 h, and then allowed to cool naturally to room temperature to obtain the varistor.
[0124] Example 3 A zinc oxide varistor ceramic comprises the following raw materials: 95.4 wt% zinc oxide, 2 wt% bismuth oxide, 1.5 wt% antimony oxide, 0.5 wt% cobalt oxide, 0.3 wt% manganese oxide, 0.2 wt% silicon oxide, and 0.1 wt% aluminum oxide; the purity of all raw materials is ≥99.5%, and the particle size is ≤10 μm.
[0125] Its preparation method includes the following steps: (1) Ingredients: Weigh each raw material according to the above mass percentage using an electronic balance (weighing accuracy ±0.1g) and set aside; (2) Wet grinding and mixing: The raw materials after batching are put into a planetary ball mill, and deionized water and polyethylene glycol (dispersant) are added. The mass ratio of raw materials, deionized water and dispersant is 100:40:1.0, the ball-to-material ratio is 8:1, the grinding balls are zirconia balls (particle size 30mm), the ball milling speed is 400 r / min, and the ball milling time is 6h to obtain a uniform slurry; (3) Drying and granulation: The slurry is placed in a spray dryer with an inlet temperature of 200 ℃, an outlet temperature of 100 ℃, and an atomization pressure of 0.5 MPa. After drying, particles with a particle size of about 120 μm are obtained. (4) Molding: The granules are placed in the molding mold and pressed by a hydraulic molding machine. The molding pressure is 25 MPa and the holding time is 30s to obtain a green body with a density of 3.0 g / cm³. (5) Debinding: Place the green body into the debinding furnace, heat it to 550 ℃ at a heating rate of 8 ℃ / min, keep it at that temperature for 2 hours, and then cool it to room temperature at a cooling rate of 5 ℃ / min to complete the debinding. (6) Sintering: The green body after debinding is placed in a sintering furnace and heated to 700 ℃ at a heating rate of 5 ℃ / min, held for 1 h, then heated to 1250 ℃ at a heating rate of 3 ℃ / min, held for 3 h. The sintering process is carried out in an air atmosphere (oxygen content 21%). Finally, the temperature is lowered to room temperature at a cooling rate of 6 ℃ / min to obtain zinc oxide varistors.
[0126] A varistor includes a zinc oxide varistor ceramic prepared in this embodiment, and electrodes disposed on both ends of the zinc oxide varistor ceramic.
[0127] The method for preparing the varistor includes: depositing silver electrodes on both ends of the varistor ceramic using a vacuum sputtering process, with a sputtering power of 150 W, a sputtering time of 10 min, and a sputtering pressure of 0.3 Pa; after the deposition is completed, the ceramic product is placed in an annealing furnace, heated to 350 ℃, held at that temperature for 1 h, and then allowed to cool naturally to room temperature to obtain the varistor.
[0128] Comparative Example 1 This comparative example uses existing conventional preparation processes (without optimizing parameters such as mixing, molding, and sintering) to prepare zinc oxide varistors according to the raw material formulation of Example 1.
[0129] Performance testing The density, grain size and distribution of the varistor ceramics prepared in Examples 1-3 and Comparative Example 1 were tested. The nonlinear coefficient, surge current carrying capacity, leakage current and voltage temperature coefficient of the varistor prepared in Examples 1-3 and Comparative Example 1 were also tested. The results are recorded in Table 1.
[0130] The leakage current is obtained by applying the nominal varistor voltage (i.e., rated voltage) to the varistor ceramic at room temperature (25℃±2℃) and reading the current value after stabilizing for 30 seconds. The voltage temperature coefficient is calculated by placing the varistor ceramic in a programmable temperature chamber and measuring the varistor voltage at -40 ℃, 25 ℃ and 85 ℃ respectively (using the voltage value under 1 mA DC current as the varistor voltage).
[0131] The voltage temperature coefficient α V The calculation formula is:
[0132] Among them, V 85 V 40 V25 These represent the varistor voltages at the corresponding temperatures.
[0133] Table 1. Performance test results of the varistors and varistors prepared in Examples 1-3 and Comparative Example 1
[0134] As shown in Table 1, the performance of the varistor ceramics and varistors in Examples 1-3 is superior to that in Comparative Example 1. They also exhibit good performance stability and batch consistency, making them suitable for high-voltage protection scenarios. This demonstrates that by rationally controlling the process parameters of each step, such as batching, mixing, molding, debinding, sintering, and electrode preparation, the present invention can effectively improve the microstructure of the varistor ceramic and enhance its density, grain uniformity, nonlinear coefficient, surge current carrying capacity, leakage current, and voltage temperature coefficient.
[0135] In the description of this specification, the references to terms such as "an embodiment," "some embodiments," "a method of implementation," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0136] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A zinc oxide varistor ceramic, characterized in that, The raw materials include: zinc oxide 90.3~95.4 wt%, bismuth oxide 2~4 wt%, antimony oxide 1.5~2.5 wt%, cobalt oxide 0.5~1.5 wt%, manganese oxide 0.3~0.8 wt%, silicon oxide 0.2~0.6 wt%, and aluminum oxide 0.1~0.3 wt%. The zinc oxide varistor ceramic has a density of ≥95% and a grain size distribution between 5 and 15 μm.
2. The zinc oxide varistor ceramic according to claim 1, characterized in that, At least one of the following conditions must be met: The nonlinear coefficient α of the zinc oxide varistor is ≥50; The surge current carrying capacity of the zinc oxide varistor is ≥20kA.
3. The zinc oxide varistor ceramic according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: The leakage current of the zinc oxide varistor is ≤ 5 μA; The zinc oxide varistor has a voltage temperature coefficient α within a temperature range of -40℃ to 85℃. V absolute value | α V | ≤0.05 % / ℃.
4. A method for preparing zinc oxide varistors as described in any one of claims 1 to 3, characterized in that, include: The raw materials are mixed with water and dispersant, and then ball-milled to obtain a slurry; The slurry is dried and granulated to obtain granulated particles; The particles are pressed into shape to obtain a green body; The green body is then subjected to debinding treatment; The debinding green body is sintered to obtain the zinc oxide varistor ceramic; The sintering includes a first sintering and a second sintering performed sequentially. The first sintering includes: heating to 600-700℃ at a heating rate of 3-5℃ / min and holding at that temperature for 1-1.5 h; The second sintering process includes heating to 1150-1250 ℃ at a heating rate of 2-3 ℃ / min and holding at that temperature for 3-5 h.
5. The method according to claim 4, characterized in that, At least one of the following conditions must be met: The mass ratio of the raw materials, deionized water, and dispersant is 100:(30~40):(0.5~1.0); The dispersant includes at least one of polyethylene glycol or sodium citrate; The ball milling speed is 300~400 r / min, and the ball milling time is 6~8 h; The ball-to-material ratio of the ball mill is 5:1 to 8:
1.
6. The method according to claim 4, characterized in that, At least one of the following conditions must be met: The inlet temperature of the drying granulation process is 180~200 ℃, and the outlet temperature is 80~100 ℃; The drying granulation includes spray drying, wherein the atomization pressure of the spray drying is 0.3~0.5 MPa; The particle size of the granulated particles is 80~120 μm.
7. The method according to claim 4, characterized in that, At least one of the following conditions must be met: The molding pressure for the compression molding is 15~25 MPa, and the holding time is 30~60 s; The pressing and forming equipment includes a hydraulic forming machine; The density of the green body is ≥2.8 g / cm³. 3 .
8. The method according to claim 4, characterized in that, The adhesive removal process involves heating the temperature to 450-550°C at a heating rate of 5-8°C / min, holding the temperature for 2-3 hours, and then cooling the temperature to room temperature at a cooling rate of 3-5°C / min.
9. A varistor, characterized in that, It includes the zinc oxide varistor ceramic as described in any one of claims 1 to 3 or the zinc oxide varistor ceramic prepared by the method described in any one of claims 4 to 8, and electrodes disposed on both ends of the zinc oxide varistor ceramic.
10. The varistor according to claim 9, characterized in that, At least one of the following conditions must be met: The electrode is formed by vacuum sputtering, wherein the power of vacuum sputtering is 100~150 W, the time of vacuum sputtering is 10~20 min, and the gas pressure of vacuum sputtering is 0.1~0.3 Pa. After deposition, the electrode also undergoes an annealing process, wherein the annealing temperature is 300~350 ℃ and the holding time is 1~1.5 h.